PENGEMBANGAN KECERDASAN MUSIKAL ANAK USIA DINI MELALUI ALAT MUSIK PERKUSI DI PAUD HABIB KECAMATAN BESITANG - Rozana, Salma; Rika Widya; Resty Madani3 (Journal of Innovation Research and Knowledge, 2025)
This study aims to improve the musical intelligence of early childhood students at PAUD Habib, Besitang District, Langkat Regency through percussion instrument games. This study uses a classroom action research method with two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data were collected through observation of the development of children's musical intelligence, which was measured using the following indicators: singing songs in groups, singing songs in time with the music, playing simple musical instruments, understanding simple musical patterns, and memorizing songs with music. The results showed a significant increase in children's musical intelligence after playing percussion instruments, with most children reaching the “Developing as Expected” and “Developing Very Well” levels in the second cycle. This study suggests that early childhood education teachers pay more attention to the duration and interaction between children in percussion music activities.